2007
DOI: 10.2116/analsci.23.219
|View full text |Cite
|
Sign up to set email alerts
|

DMPO-OH Radical Formation from 5,5-Dimethyl-1-pyrroline N-Oxide (DMPO) in Hot Water

Abstract: The spin-trapping method with 5,5-dimethyl-1-pyrroline Noxide (DMPO) has been widely accepted as an assay method to measure hydroxyl radical formation, and to detect the hydroxyl radical scavenging activity of a compound. Although unstability of DMPO is claimed because it turns yellow with time even at -20˚C in a sealed tube under vacuum, 1 the basic chemistry of DMPO and DMPO-OH has not been well understood.In a previous work, 2 we noticed very weak DMPO-OH signals in the baseline of a negative control spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 7 publications
(6 reference statements)
1
14
2
Order By: Relevance
“…12 A and B). This observation did not coincide with a previous report by Shoji et al (15) who reported that the formation of DMPO-OH was suppressed under an argon atmosphere, using ultra-pure water, or the addition of EDTA; however, the addition of α-mannitol or DMSO did not affect the formation of DMPO-OH. In contrast to the previous report, the formation of DMPO-OH was suppressed by the relatively high concentration of • OH scavengers in this paper, in which the experimental system contained 0.05 mM DTPA.…”
Section: Resultscontrasting
confidence: 98%
“…12 A and B). This observation did not coincide with a previous report by Shoji et al (15) who reported that the formation of DMPO-OH was suppressed under an argon atmosphere, using ultra-pure water, or the addition of EDTA; however, the addition of α-mannitol or DMSO did not affect the formation of DMPO-OH. In contrast to the previous report, the formation of DMPO-OH was suppressed by the relatively high concentration of • OH scavengers in this paper, in which the experimental system contained 0.05 mM DTPA.…”
Section: Resultscontrasting
confidence: 98%
“…Although the yield of DMPO-OH was formed dependently on the temperature under the H(Ϫ)L(ϩ) and H(Ϫ)L(Ϫ) conditions, the level of DMPO-OH in the absence of H 2 O 2 was much lower than that of in the presence of H 2 O 2 . A trace level of DMPO-OH detected under the H(Ϫ)L(ϩ) and H(Ϫ)L(Ϫ) conditions might be formed by the reaction of DMPO and dissolved oxygen at high water temperatures, as reported in a previous study (19). These findings suggest that photolysis and autolysis of H 2 O 2 are endothermal reactions, so that the yield of hydroxyl radical generated by photolysis of H 2 O 2 can be controlled by the temperature of the H 2 O 2 as well as the by the concentration of the H 2 O 2 .…”
Section: Discussionsupporting
confidence: 71%
“…The obtained spectra agreed with those of DMPO-OH. 15,16,19) The ESR spectra obtained from the HPX-XOD system are shown as B in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…An Mn 2þ marker built into the ESR spectrometer, which gave reversed-phase signals of Mn 2þ , was simultaneously analyzed as an external reference. 15) The parameters for operating the ESR spectrometer were as follows, unless otherwise stated: microwave power, 4.0 mW; scan field, 335:3 AE 5:0 mT; modulation frequency, 100 kHz; modulation width, 0.1 mT; scan time, 2 min; time constant, 0.1 s; amplitude, 250; dial number of the marker, 650. All spectra were acquired at room temperature.…”
Section: )mentioning
confidence: 99%